mTORC1-independent TFEB activation via Akt inhibition promotes cellular clearance in neurodegenerative storage diseases - Michela Palmieri (Nature Portfolio, 2017)
The transcription factor EB (TFEB) is a master regulator of lysosomal biogenesis. Here authors show that trehalose, an mTOR-independent autophagy inducer, alleviates the pathological phenotypes in a mouse model of neurodegenerative disease. Trehalose acts by inhibiting Akt, which normally suppresses TFEB via an mTORC1-independent mechanism.